Pengaruh Tekanan Waktu, Konflik Peran dan Integritas terhadap Kualitas Audit dengan Stres Kerja Sebagai Variabel Intervening - Irwan Hidayat Ibrahim; Haliah Haliah; Abdul Hamid Habbe (Politeknik Ganesha Medan, 2023)
This study aims to analyze the effect of time pressure, role conflict, and integrity on audit quality with work stress as an intervening variable in the auditors of the Inspectorate of West Sulawesi Province. The research population totaled 100; samples were taken using the slovin technique, so a sample of 60 was obtained. The data source in this study uses primary data from the questionnaire results, namely data obtained based on the results of filling out the auditor's questionnaire at the Inspectorate of West Sulawesi Province. Data analysis in this study is Structural Equation Modeling- Partial Least Squares (SEM-PLS). The results of this study indicate that time pressure and role conflict have no significant effect on audit quality. Meanwhile, auditor integrity and work stress significantly affect audit quality. Time pressure and auditor integrity do not affect audit quality through work stress. Besides that. Role conflict affects audit quality through work stress as an intervening. This research has implications for auditors to improve performance which can support success in auditing so that agencies will be motivated to improve their performance.